The Prevalence of Salmonella and Campylobacter on Broiler Meat at Different Stages of Commercial Poultry Processing - Hudson T. Thames; Courtney A. Fancher; Mary G. Colvin; Mika McAnally; Emily Tucker; Li Zhang; Aaron S. Kiess; Thu T. N. Dinh; Anuraj T. Sukumaran (Animals, 2022)
In poultry processing, Salmonella and Campylobacter contaminations are major food safety concerns. Peracetic acid (PAA) is an antimicrobial commonly used in commercial poultry processing to reduce pathogen prevalence so as to meet the USDA-FSIS performance standards. The objective of this study was to determine the prevalence of Salmonella and Campylobacter on broiler meat in various steps of commercial poultry processing in plants that use PAA. Post-pick, pre-chill, post-chill, and drumstick chicken samples were collected from three processing plants and mechanically deboned meat (MDM) was collected from two of the three plants. Each plant was sampled thrice, and 10 samples were collected from each processing step during each visit. Among the 420 samples, 79 were contaminated with Salmonella and 155 were contaminated with Campylobacter. Salmonella and Campylobacter contamination on the post-pick samples averaged 32.2%. Significant reductions in Salmonella and Campylobacter were observed in pre-chill to post-chill samples, where the prevalence was reduced from 34% and 64.4% to nondetectable limits and 1.1%, respectively (p < 0.001). Salmonella and Campylobacter remained undetectable on the drumstick samples in all three processing plants. However, the prevalence of Salmonella and Campylobacter on MDM was similar to the post-pick prevalence, which suggests substantial cross-contamination from post-chill to MDM.